1976
DOI: 10.1128/jb.126.1.327-337.1976
|View full text |Cite
|
Sign up to set email alerts
|

Protonmotive force as the source of energy for adenosine 5'-triphosphate synthesis in Escherichia coli

Abstract: Net synthesis of adenosine 5'-triphosphate (ATP) in energy-depleted cells of Escherichia coli was observed when an inwardly directed protonmotive force was artificially imposed. In wild-type cells, ATP synthesis occurred whether the protonmotive force was dominated by the membrane potential (negative inside) or the pH gradient (alkaline inside). Formation of ATP did not occur unless the protonmotive force exceeded a value of 200 mV. Under these conditions, no ATP synthesis was found when cells were exposed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0
1

Year Published

1977
1977
1993
1993

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(30 citation statements)
references
References 40 publications
1
24
0
1
Order By: Relevance
“…Maloney et al (14,15) recently reported ATP synthesis energized by an artificially imposed membrane potential or proton gradient in whole cells of Streptococus lactis. Similar results have been obtained using E. coli cells (5,35). Recently, an artificially imposed membrane potential (32) or proton gradient (33), in addition to oxidation, was shown to drive the synthesis of ATP in isolated membrane vesicles of E. coli.…”
Section: Time ( Sec )supporting
confidence: 76%
See 4 more Smart Citations
“…Maloney et al (14,15) recently reported ATP synthesis energized by an artificially imposed membrane potential or proton gradient in whole cells of Streptococus lactis. Similar results have been obtained using E. coli cells (5,35). Recently, an artificially imposed membrane potential (32) or proton gradient (33), in addition to oxidation, was shown to drive the synthesis of ATP in isolated membrane vesicles of E. coli.…”
Section: Time ( Sec )supporting
confidence: 76%
“…Membrane vesicles from either AN120 or AN382 failed to synthesize ATP coupled to either respiration or an artificially imposed ApH ( Table 2). Wilson et al (35) reported similar results using whole cells of AN120. It is very likely that the BFDF1 of AN382 cannot mediate proton movement, so that an electrochemical proton gradient cannot couple to ATP synthesis, nor can hydrolysis of ATP generate a protonmotive force.…”
Section: Resultsmentioning
confidence: 61%
See 3 more Smart Citations